Experimental investigatopn of temperature-induced performance degradation in BLDC motors for electric vehicle applications - Aris Budi Sulistyo; I Wayan Yogi Arta (Politeknik Negeri Lhokseumawe, 2026)
The performance of Brushless Direct Current (BLDC) motors in electric vehicle applications is significantly affected by thermal operating conditions; however, experimental studies that directly evaluate temperature-induced performance degradation under real prototype operation remain limited. This study aims to experimentally evaluate the effect of operating temperature on the torque and power characteristics of a BLDC motor integrated into an electric vehicle prototype developed in Bali Land Transportation Polytechnic, Bali. The motor was tested under controlled conditions at rotational speeds ranging from 750 to 2000 rpm. Electrical current, operating temperature, torque, and output power were measured directly, while mechanical output power was calculated using rotational dynamics principles. The results showed that increasing motor speed caused a continuous rise in current and operating temperature, from 34.8 °C at 750 rpm to 87.3 °C at 2000 rpm. Mechanical output power increased with speed and reached a maximum value of 7.13 HP within the range of 1250–1500 rpm, before decreasing at higher speeds despite further increases in current and angular velocity. This reduction was accompanied by a significant decrease in torque, indicating thermally induced electromagnetic performance degradation. The findings identify an optimal operating region limited by temperature and highlight the importance of thermal management for maintaining performance and reliability in electric vehicle propulsion systems.